1992
DOI: 10.1021/j100191a068
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium NMR and x-ray crystallographic studies of guest and host motions in the thiourea/1,4-di-tert-butylbenzene inclusion compound

Abstract: 5121 (23) Clegg, H. P.; Rowlinson, J. S. Faraday SOC. Tram. 1955,51,1333. (24) Gugnoni, R. J.; Eldrige, J. w.; Okay, V. C.; Lee, T. J. AIChE J. 1974, (25) Aftienjew, J.; Zawisza, A. J. Chem. Thermodyn. 1977, 9, 153. (26) Haselden, G. G.; Newitt, D. M.; Shah, S. M. Proc. R. SOC. A 1951, (19) Prausnitz, J. M.; Lichtenthaler, R. N.; Gomes de Azevedo, E.Deuterium nuclear magnetic resonance (NMR) spectra and spin-lattice relaxation times are used to investigate the guest and host molecular dynamics of solid 1 ,4-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 10 publications
3
45
0
Order By: Relevance
“…Previous work by Ripmeester and Ratcliffe (8,9) demonstrated that, in trimethyl and tetramethylammonium salts, both CS and C, rotation may be in the intermediate exchange region at low temperatures. It was also shown that in some (CH,),CX systems Cj rotation is rapid at low temperatures, whereas C3 rotation is slow (7,12). In principle it should be possible to reproduce the spectra shown in Fig.…”
Section: Phetzyltrimethylphosphonium-d3 Iodide (6)mentioning
confidence: 91%
See 1 more Smart Citation
“…Previous work by Ripmeester and Ratcliffe (8,9) demonstrated that, in trimethyl and tetramethylammonium salts, both CS and C, rotation may be in the intermediate exchange region at low temperatures. It was also shown that in some (CH,),CX systems Cj rotation is rapid at low temperatures, whereas C3 rotation is slow (7,12). In principle it should be possible to reproduce the spectra shown in Fig.…”
Section: Phetzyltrimethylphosphonium-d3 Iodide (6)mentioning
confidence: 91%
“…It is often relatively easy to introduce ' H into a variety of molecular systems (4), and ' H N M R techniques can be used to study molecular dynamics with exchange rates, k, ranging from lo-' to lo9 s-' (1). The molecular motions of numerous solid trimethyl systems of the type (CH,),M, where M is CSH (3,CBr ( 6 ) , CC1, C1, CCHO (7), NH+, NCH,+ (8,9), S=O+ (lo), N (1 I), and CC,H, (12), have been studied by deuterium N M R spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1) Most of the thiourea inclusion complexes showed incommensurate structural properties. 7,8) Temperature-dependent phase transition of a thiourea inclusion complex from conventional rhombohedral tunnel structure to the monoclinic form at low temperature was also reported. 9) Complexation property of thiourea has been applied for extraction and stabilization of foods and medicinal drugs.…”
mentioning
confidence: 93%
“…A class of molecules that has been rewarding to study are single-and fused-ring aromatic structures containing one or two t-butyl groups. [1][2][3][4][5][6][7][8] We have synthesized the organic molecule 3-t-butylchrysene, determined the molecular ͑Fig. 1͒ and crystal ͑Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, deuteron NMR spectroscopy, deuteron NMR relaxation rate studies, and x-ray diffraction have teamed up to better model the relationship between the complicated motions and aromatic ring distortions in 9-t-butylanthracene 27 as well as the dynamical behavior of t-butyl reorientation in 1,4-di-t-butylbenzene in inclusion compounds. 2 The main purposes of this paper are ͑1͒ to present the synthesis, the x-ray diffraction, and the temperature and frequency dependence of the proton spin-lattice relaxation rate in solid 3-t-butylchrysene, ͑2͒ to review the current dynamical model for t-butyl and methyl group motion and recast it in a more general way, and ͑3͒ to compare proton NMR relaxometry and x-ray diffraction studies of three other molecular solids with the results in 3-t-butylchrysene presented here. The three other systems are 4-methyl-2,6-di-tbutylphenol, 1,4-di-t-butylbenzene, and polymorph A of 2,6-di-t-butylnaphthalene.…”
Section: Introductionmentioning
confidence: 99%